Organization of Marketing in the New Economic Conditions: Case of the Republic of Croatia - Meler, Marcel; Turkalj, Zeljko (Marketing & Menedzsment, 2019)
The situation (social and economic) in the countries of the so called real existing socialism results in total collapse. It is beyond any doubt that this collapse was to a great extent caused by the inefficient management, that is, by the economic system based and established on the state or public ownership. In such a "relation without an owner" no room was left for the demonstration of the abilities of an individual - initiative, creativity, readiness to take risks, and everything else that characterizes the free market economy of the western world.